Replacing chemical fertilizers with organic alternatives: A comparison of performance of Phosphate Rich Organic Manure and Di Ammonium Phosphate on mustard - PO Suresh; NR Patel; R Jat; RA Pania; PB Vaishnav (Journal of Oilseed Brassica, 2026)
Combining rock phosphate with natural organics facilitates the release of phosphorus (P) from the mineral in a form thatis easily available to plants. Replacing chemical fertilizers with such organic alternative is expected to improve soilorganic matter content and increase agricultural soil sustainability. Phosphorus release rate from rock phosphate inpresence of organic matter containing tobacco waste is observed to be better than or at par with that due to activity ofP solubilizing bacteria. A field experiment was conducted to study the production and nutrient cluster of Indian mustardinfluenced by the organic source of P - Phosphate Rich Organic Manure (PROM) and the chemical fertilizer DiammoniumPhosphate (DAP). Phosphorous release rate from rock phosphate by bacterial activity is compared with that by organicacids present in tobacco to see higher release of P by the later. Results indicated clear possibility for partially replacingchemical phosphatic fertilizers with organic alternatives. Using rock phosphate composted with organic manure turnsout to be an excellent alternative for chemical phosphatic fertilizers. Higher yield parameters are obtained with PROMand DAP in combination as P source for mustard crop. A combination of PROM as source of 66% of P requirement andDAP as source of the rest of the P requirement gave best results in the efficacy studies, indicating possibilities inreplacement of chemical fertilizers with organic alternatives and hence reducing consumption of rock phosphate mineralfor production of chemical fertilizers.